The Effects of Repeat-Dose Doxorubicin on Cardiovascular Functional Endpoints and Biomarkers in the Telemetry-Equipped Cynomolgus Monkey - Engwall, Michael J.; Everds, Nancy; Turk, James R.; Vargas, Hugo M. (Frontiers in Cardiovascular Medicine, 2021)
Purpose Doxorubicin (Dox)-related heart failure has been recognized as a serious complication of cancer chemotherapy. This paper describes a cardiovascular safety pharmacology study with chronic dosing of Dox in a non-human primate model designed to characterize the onset and magnitude of left ventricular dysfunction (LVD) using invasive and non-invasive methods.Cynomolgus monkeys (N=12) were given repeated intravenous injections of Dox over 135 daysThere was variable sensitivity to the onset of treatment effects, for example 25% of Dox-treated animals exhibited LVD (e.g. decreases in ejection fraction) following50-63 days (cumulative dose: 8-9 mg/kg) on study. All animals deteriorated into heart failure with additional dosing days (total cumulative dose: 11-17 mg/kg). Reductions in arterial pressure and cardiac contractility, as well as QTc interval prolongation, was evident following Dox-treatment. Both cTnI and NT-proBNP were inconsistently higher at the end of the study in animals with LVD.Measurements collected from control animals were consistent and stable over the same time 3 frame. Minimal to mild, multifocal, vacuolar degeneration of cardiomyocytes was observed in of 12 animals receiving Dox and 0 of 12 animals receiving vehicle.This repeat-dose study of Dox treatment in the cynomolgus monkey demonstrated a clinically relevant pattern of progressive heart failure. Importantly, the study revealed how both telemetry and non-invasive echocardiography measurements could track the gradual onset of LVD.